Ice volume estimates from ground-penetrating radar surveys, Wedel Jarlsberg Land glaciers, Svalbard - Navarro Valero, Francisco José; Martín Español, Alba; Lapazaran Izargain, Javier Jesús; Grabiec, M.; Otero García, Jaime; Vasilenko, Evgeniy; Puczko, D. (E.T.S.I. Telecomunicación (UPM), 2013)
One of the aims of the SvalGlac project is to obtain an improved estimate, with reliable error estimates, of the volume of Svalbard glaciers and their potential contribution to sea level rise. As part of this work, we present volume calculations, with detailed error estimates, for eight glaciers on Wedel Jarlsberg Land, southern Spitsbergen, Svalbard. The volume estimates are based upon a dense net of GPR-retrieved ice thickness data collected over several field campaigns spanning the period 2004-2011. The total area and volume of the ensemble are 502.9±18.6 km2 and 80.72±2.85 km3, respectively. Excluding Ariebreen (a tiny glacier, menor que 0.4 km2 in area), the individual areas, volumes and average ice thickness lie within 4.7-141.0 km2, 0.30-25.85 km3 and 64-183 m, respectively. The maximum recorded ice thickness, ca. 619±13 m, is found in Austre Torellbreen. To estimate the ice volume of small non-echo-sounded tributary glaciers, we used a function providing the best fit to the ice thickness along the centre line of a collection of such tributaries where echo-soundings were available, and assuming parabolic cross-sections. We did some tests on the effect on the measured ice volumes of the distinct radio-wave velocity (RWV) of firn as compared to ice, and cold versus temperate ice, concluding that the changes in volume implied by such corrections were within the error bounds of our volume estimate using a constant RWV for the entire glacier inferred from common mid-point measurements on the upper ablation area.